Most influential women in politics in Trinidad & Tobago 1946-2002 - Chuckaree, Ramona (Network of NGOs for the Advancement of Women Port of SpainTT, 2002)
Highlights women who have served at the highest level in the Houses of Parliament in order to show that women can make and have made a tremendous contribution when given the opportunity to do so.